Conserver la faune sauvage de la péninsule malaise : de la Malaya britannique à la Malaisie indépendante - Mathieu Guérin (VertigO)
Peninsular Malaysia hosts a remarkable biodiversity and has succeeded in maintaining sustainable populations of endangered species. Historical sources show that this achievement was made possible thanks to a conservation apparatus set up during the British colonial period, which continued and developed further after Independence. Under the pressure of colonists interested in wildlife conservation, such as big game hunter Theodore Hubback, the Malay States under British rule drafted protection laws, established parks and reserves -- including the King George V National Park -- and set up a Game Department charged with pest control, law enforcement, parks management and wildlife conservation. The British Game Wardens were backed by concerned Malaysians who were able to take over after Independence despite the lack of means allocated to wildlife protection. The Malayan Nature Society, founded in 1940 by the federal Chief Game Warden, assisted the Game Department in its task. While the Society remained a British club up to the early 1970s, some of its few Malaysian members became very influential in independent Malaysia. After Independence, the Society was at the centre of a network that connected conservationists, scientists, Game Wardens and decision makers. It was this network of institutions and individuals that allowed Malaysia not only to pursue the conservation agenda set by the British, but also to draw its own conservation policy.